Accent variation in Indian English: a folk linguistic study - Regnoli, Giuliana (VarioLingua, 2021)
This is the first major sociolinguistic work on Indian diasporic communities in Germany. The study shows that metalanguage allows to understand what sociolinguistic stereotypes are at stake in diasporic communities and what criteria are made use of in such discriminations.
Description based on publisher supplied metadata and other sources
Keywords: Hochschulschrift; Akzent; Englisch; Indien